Low-shrinkage high-airtightness concrete and preparation method thereof

By using special composite cementitious materials, combined with modified components such as high-Belite cement clinker, iron aluminate cement clinker, and fine powders such as submicron fume, predispersed carbon nanotubes, the microstructure of concrete is optimized, and the problem of poor durability of existing cementitious materials in complex environments is solved, and low shrinkage, high airtightness and excellent mechanical properties are achieved.

CN119797861AActive Publication Date: 2025-04-11JIAHUA SPECIAL CEMENT
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510003276.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Existing gelling materials cannot meet the more stringent construction and service requirements in complex and variable service environments, resulting in poor durability and short service life.

Method used

Special composite cementitious materials are used, including high-Belite cement clinker, iron aluminate cement clinker, lightly flammed magnesium oxide, submicron fume, fly ash, glass powder and predispersed carbon nanotubes. The microstructure and performance of concrete are optimized through the combination of modified components and fine powders.

Benefits of technology

It achieves low shrinkage, high airtightness and excellent mechanical properties, improves the compressive strength, frost resistance, seepage resistance, wear resistance and corrosion resistance of concrete, and adapts to the needs of complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226081460000071
    Figure BDA0005226081460000071
  • Figure BDA0005226081460000081
    Figure BDA0005226081460000081
  • Figure BDA0005226081460000082
    Figure BDA0005226081460000082
Patent Text Reader

Abstract

The invention discloses low-shrinkage high-air-tightness concrete and a preparation method thereof. The air-tightness concrete comprises the following raw materials by weight: 687-746 kg / m < 3 > of a special composite cementing material; sand: 848-893 kg / m < 3 >; stone: 1036-1091 kg / m < 3 >; 165-171 kg / m < 3 > of water; 3.9-4 kg / m < 3 > of a water reducing agent; a pre-dispersed carbon nanotube: 0.687 to 0.746 kg / m < 3 >; and 0.206 to 0.224 kg / m < 3 > of diethanolisopropanolamine. The airtight concrete is high in workability and overall later strength, good in mechanical performance, shrinkage resistance and airtight performance and capable of meeting complex and changeable service environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to low-shrinkage and high-airtightness concrete and a preparation method thereof. Background Art

[0002] As the most widely used building material, the durability of concrete has always been one of the research focuses in the field of concrete materials science and technology. Concrete durability can not only well reflect the safety, reliability and service life of concrete structures under various environmental conditions, but also its evaluation and enhancement can ensure the stability and sustainability of concrete in various application scenarios.

[0003] The durability process of concrete materials is relatively complex, but it is basically related to the pore structure of concrete and the material transfer in the pore structure, so the durability of concrete mainly depends on permeability. Gas permeability is a direct physical representation of the ability of gas media to migrate in cement-based porous materials under pressure. It is an ideal physical parameter to measure the durability and density of concrete materials. As a durability performance indicator, it has been widely used in many engineering structures in the field of building materials, such as tunnel lining structures containing gas, vacuum pipelines, concrete containment in nuclear power projects, radiation-resistant concrete, reinforced concrete structures, and other buildings that require high airtightness.

[0004] Research scholars have conducted relevant research on the air tightness of concrete. Patent document CN114573288A discloses a high-air-tightness concrete. By adding characteristic components and pre-treated highly absorbent resins to the concrete components, the concrete composition and microscopic pore structure are optimized, so that high air tightness and stability can be maintained in a long-term low-vacuum environment; Patent document CN114133190A discloses an airtight concrete. By using machine-made sand with a suitable ratio, an airtight agent and an expansion agent, the air tightness and impermeability of the concrete are increased to meet the requirements of tunnel construction; Patent document CN110698137A improves the concrete microstructure and introduces stable elastic bubbles by adding mineral admixtures and special air-entraining agents, thereby improving the ability to resist gas penetration and pressurized water penetration.

[0005] The above-mentioned technical means for preparing airtight concrete mainly improve the airtightness of concrete by adding characteristic components, mineral admixtures, internal curing materials, controlling the quality of concrete materials, optimizing the concrete mix ratio, etc. However, the most important cementitious materials all use ordinary silicate-based cementitious materials without any changes. However, with the development of modernization and the needs of engineering construction in special fields, more stringent construction and service environments, higher functions and gas permeability resistance requirements pose new challenges to airtight concrete. As the main component of concrete, cementitious materials have a good improvement effect on the pore structure due to their hydration products, can provide strong structural support, promote the durability of concrete and realize the diversity of design structures, and are often used. Conventional ordinary silicate-based cementitious materials lack engineering application targeting, cannot meet the complex and changeable service environment, have poor durability and short service life. Therefore, it is urgent to design a low-shrinkage and high-airtightness concrete from the perspectives of cementitious material composition, structure and performance to adapt to more complex engineering environments. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a low-shrinkage and high-airtightness concrete and a preparation method thereof, so as to at least solve part of the above-mentioned technical problems.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] In one aspect, a low shrinkage and high airtightness concrete is provided, comprising the following raw materials prepared by weight:

[0009] Special composite cementitious material: 687~746kg / m 3 ;

[0010] Sand: 848~893kg / m 3 ;

[0011] Stone: 1036~1091kg / m 3 ;

[0012] Water: 165~171kg / m 3 ;

[0013] Water reducing agent: 3.9~4kg / m 3 ;

[0014] Pre-dispersed carbon nanotubes: 0.687~0.746kg / m 3 ;

[0015] Diethanol monoisopropanolamine: 0.206~0.224kg / m 3 .

[0016] Furthermore, the special composite gelling material comprises the following components by mass percentage:

[0017] High belite cement clinker: 55-61wt%;

[0018] Ferroaluminate cement clinker: 6-12wt%;

[0019] Light-burned magnesium oxide: 3-5wt%;

[0020] Submicron silica fume: 7-10wt%;

[0021] Fly ash: 9-12wt%;

[0022] Glass powder: 6-8wt%;

[0023] Gypsum: 3wt%.

[0024] Furthermore, the weight percentages of minerals in the high-belite cement clinker are as follows: 2 S: 50-60 wt%, C 3 S: 17-25 wt%, C 4 AF: 13~19wt%C 3 A: 2-5wt%; the specific surface area of ​​the high-belite cement clinker is 350-370m 2 / kg, 3d compressive strength ≥12MPa.

[0025] Furthermore, the weight percentages of minerals in the ferroaluminate cement clinker are as follows: 35~55wt%C 2 S: 15-35 wt%, C 6 AF 2 : 15-30wt%; the specific surface area of ​​the ferroaluminate cement clinker is 370-390m 2 / kg, 3d compressive strength ≥42MPa.

[0026] Furthermore, the content of magnesium oxide in the light-burned magnesium oxide is ≥85wt%, the content of active magnesium oxide is ≥65wt%, and the particle size is ≤40μm; the SiO 2 Content>93wt%, specific surface area 23000m 2 / kg, 7d activity index ≥105%; the fly ash is Class I fly ash, with a specific surface area of ​​398m 2 / kg; the glass powder is waste quartz glass powder with a specific surface area of ​​450m 2 / kg; the gypsum is natural gypsum or mixed gypsum, the anhydrite content in the natural gypsum or mixed gypsum is not more than 50wt% of the total gypsum, and the specific surface area of ​​the gypsum is 317~421m 2 / kg.

[0027] Furthermore, the sand is zone II sand formed by mixing river sand with a particle size of 0 to 1.18 mm and machine-made sand with a particle size of 0.15 to 4.75 mm. The river sand and machine-made sand are mixed in a mass ratio of 4:6, and the apparent density is 2573 kg / m 3 , bulk density is 1769kg / m 3 , the fineness modulus is 2.6.

[0028] Furthermore, the stone is a continuously graded crushed stone with a particle size distribution between 5 and 10 mm, a mud content of 0.7 wt%, a crushing value of 5.2%, and an apparent density of 2782 kg / m 3 , bulk density is 1605kg / m 3 .

[0029] Furthermore, the water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate greater than 30%; the solid content of the diethanol monoisopropanolamine is ≥85wt%, and the pH value is 10.24.

[0030] Furthermore, the pre-dispersed carbon nanotubes are obtained by pre-dispersing carbon nanotubes with a length of 100 to 200 μm and a diameter of 7 to 9 nm, and the preparation method is as follows:

[0031] (1) Weigh carbon nanotubes, polyvinyl pyrrolidone dispersant, and deionized water in a mass ratio of 0.1:0.3:100 for later use;

[0032] (2) adding carbon nanotubes and polyvinyl pyrrolidone dispersant into deionized water, stirring, sealing, and ultrasonically treating, followed by high pressure homogenization to obtain a pre-dispersed solution;

[0033] (3) freeze-drying the pre-dispersed liquid until deionized water is removed, and then placing it in a high-temperature drying oven to remove the polyvinyl pyrrolidone dispersant to obtain pre-dispersed carbon nanotubes;

[0034] Preferably, the ultrasonic treatment in (2) is repeated 6 times, and each ultrasonic treatment lasts for 5 minutes;

[0035] Preferably, the temperature of the high temperature drying oven (3) is 600° C., and the treatment time is 3 h.

[0036] On the other hand, a method for preparing low shrinkage and high airtightness concrete is provided, comprising the following steps:

[0037] Step 1: Weigh the pre-dispersed carbon nanotubes according to the mass ratio for use, and weigh the special composite gelling material with a mass of 10 times the mass of the pre-dispersed carbon nanotubes and 81.6 times the mass of isopropanol; divide the isopropanol into two parts, add the pre-dispersed carbon nanotubes to one part of the isopropanol, stir to dissolve and ultrasonically disperse to obtain a first mixture, then add the special composite gelling material and the other part of the isopropanol to the first mixture, stir to dissolve and ultrasonically disperse to obtain a second mixture; place the second mixture in a high-temperature drying oven to remove the isopropanol, and obtain a gelling material-CNT dry powder;

[0038] Preferably, when the pre-dispersed carbon nanotubes are added to a portion of isopropanol, stirred to dissolve and ultrasonically dispersed, the ultrasonic time is 30 minutes;

[0039] Preferably, when the special composite gelling material and another portion of isopropanol are added to the first mixture, stirred to dissolve and ultrasonically dispersed, the ultrasonic time is 90 minutes;

[0040] Preferably, the temperature of the high temperature drying oven is 100±5°C and the treatment time is 24h;

[0041] Step 2: Weigh sand, gravel, water reducing agent, diethanol monoisopropanolamine, water and the remaining special composite gelling material according to the mass ratio for use, and the mass of the remaining special composite gelling material is the total mass of the special gelling material minus the mass of the special composite gelling material corresponding to the gelling material-CNT dry powder prepared in step 1;

[0042] Step 3: Mix the remaining special composite gelling material in step 2 and the gelling material-CNT dry powder prepared in step 1 evenly; then add the weighed sand and gravel and continue to mix evenly to obtain a mixed dry material;

[0043] Step 4: The water reducing agent, diethanol monoisopropanolamine and water weighed in step 2 are fully mixed and stirred with the mixed dry materials to obtain a mixture; the mixture is poured into a mold, vibrated to compact, and then covered with a film for curing in an environment of 18°C ​​to 22°C, and low shrinkage and high airtightness concrete is obtained after molding and hardening.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The special composite cementitious material used in the present invention is mainly composed of high-belite cement clinker with low hydration heat, small shrinkage rate, good high-temperature stability and excellent long-term mechanical properties. It is modified by introducing an appropriate amount of light-burned magnesium oxide and ferroaluminate cement clinker, and the micro-expansion characteristics of light-burned magnesium oxide and ferroaluminate cement clinker are used to effectively compensate for the shrinkage of high-belite cement clinker, so that the concrete matrix has a lower hydration volume shrinkage rate; the hydration of the high iron phase in the ferroaluminate cement clinker can accelerate C 2The hydration of S and the synergistic hydration reaction with high-belite cement clinker make the concrete structure more compact, promote strength development, and make it have high strength, high frost resistance, high impermeability, wear resistance and corrosion resistance. It can also further improve the adaptability of the airtight concrete prepared by the special composite cementitious material to complex environments. At the same time, by adding a specific proportion of fly ash and glass powder, the lubricity and dispersibility of the special composite cementitious material are improved, and the workability and overall later strength of the concrete are improved.

[0046] 2. The present invention controls the particle size of each material. The submicron silica fume and pre-dispersed carbon nanotubes in the special composite cementitious material can be used as fine powder to fill the pores of other materials to improve the density of the matrix. At the same time, the carbon nanotubes are pre-dispersed to effectively reduce the degree of entanglement between the carbon nanotubes without damaging the structure of the carbon nanotubes, making their network structure loose, and disperse them in the particles of the special composite cementitious material, which is conducive to achieving uniform dispersion of the carbon nanotubes, effectively filling the micropores generated after cement hydration, and playing a good bridging and filling role in the internal pores, enhancing the density of the matrix, and effectively inhibiting the development of microcracks, thereby significantly improving the mechanical properties of concrete and improving the shrinkage resistance and airtightness of concrete.

[0047] 3. The particle size distribution of the special composite cementitious material of the present invention is reasonable. Sand and gravel are used as fine aggregate and coarse aggregate respectively. The components produce an interactive superposition effect, complement each other, and promote each other, so that the hydrated cementitious material is continuously dense. The pre-dispersed carbon nanotubes and diethanol monoisopropanolamine (DEIPA) are used together, and DEIPA is used to treat Fe in the system. 3+ The complexation effect of DEIPA, that is, the effective activation of the high-content iron phase in the two clinker systems, can further enhance the hydration reaction of the ferrite phase in the slurry under the synergistic effect with gypsum, accelerate the consumption of DEIPA and the formation of ettringite (AFt) and monosulfoaluminate (AFm) in the hydration products, promote the dissolution of mineral admixtures, optimize the pore size distribution, densify the concrete microstructure, and maintain excellent airtightness and volume stability at all stages. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0049] Example 1

[0050] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete of the present invention is shown in Table 1 below.

[0051] Table 1

[0052] raw material <![CDATA[Weight (kg / m 3 )]]> Special composite cementitious materials 687 sand 893 Stone 1091 water 165 Water reducing agent 3.9 Pre-dispersed carbon nanotubes 0.687 Diethanol Monoisopropanolamine 0.206

[0053] In this embodiment, the specific composition of the special composite cementitious material is shown in Table 2 below.

[0054] Table 2

[0055] raw material Mass percentage (wt%) High Belite Cement Clinker 61 Ferroaluminate cement clinker 6 Light Burnt Magnesium Oxide 5 Submicron silica fume 10 Fly ash 9 Glass powder 6 plaster 3

[0056] Example 2

[0057] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete of the present invention is shown in Table 3 below.

[0058] Table 3

[0059] raw material <![CDATA[Weight (kg / m 3 )]]> Special composite cementitious materials 746 sand 848 Stone 1036 water 171 Water reducing agent 4 Pre-dispersed carbon nanotubes 0.746 Diethanol Monoisopropanolamine 0.224

[0060] In this embodiment, the specific composition of the special composite cementitious material is shown in Table 4 below.

[0061] Table 4

[0062] raw material Mass percentage (wt%) High Belite Cement Clinker 61 Ferroaluminate cement clinker 6 Light Burnt Magnesium Oxide 5 Submicron silica fume 10 Fly ash 9 Glass powder 6 plaster 3

[0063] Example 3

[0064] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete of the present invention is shown in Table 5 below.

[0065] Table 5

[0066] raw material <![CDATA[Weight (kg / m 3 )]]> Special composite cementitious materials 687 sand 893 Stone 1091 water 165 Water reducing agent 3.9 Pre-dispersed carbon nanotubes 0.687 Diethanol Monoisopropanolamine 0.206

[0067] In this embodiment, the specific composition of the special composite cementitious material is shown in Table 6 below.

[0068] Table 6

[0069] raw material Mass percentage (wt%) High Belite Cement Clinker 55 Ferroaluminate cement clinker 12 Light Burnt Magnesium Oxide 3 Submicron silica fume 7 Fly ash 12 Glass powder 8 plaster 3

[0070] Example 4

[0071] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete of the present invention is shown in Table 7 below.

[0072] Table 7

[0073]

[0074]

[0075] In this embodiment, the specific composition of the special composite cementitious material is shown in Table 8 below.

[0076] Table 8

[0077] raw material Mass percentage (wt%) High Belite Cement Clinker 55 Ferroaluminate cement clinker 12 Light Burnt Magnesium Oxide 3 Submicron silica fume 7 Fly ash 12 Glass powder 8 plaster 3

[0078] Comparative Example 1

[0079] The specific composition of the concrete of this comparative example is shown in Table 9 below.

[0080] Table 9

[0081] raw material <![CDATA[Weight (kg / m 3 )]]> Cementitious materials 687 sand 893 stone 1091 water 165 Water reducing agent 3.7

[0082] In this comparative example, the specific composition of the cementitious material is shown in Table 10 below.

[0083] Table 10

[0084] raw material Mass percentage (wt%) Ordinary Portland Cement (PO42.5) 70 Fly ash 20 Silica Fume 10

[0085] Comparative Example 2

[0086] The specific composition of the concrete of this comparative example is shown in Table 11 below.

[0087] Table 11

[0088]

[0089]

[0090] In this comparative example, the specific composition of the cementitious material is shown in Table 12 below.

[0091] Table 12

[0092] raw material Mass percentage (wt%) Ordinary Portland Cement (PO42.5) 70 Fly ash 20 Silica Fume 10

[0093] Test Case

[0094] After the concretes obtained in Examples 1 to 4 and Comparative Examples 1 and 2 were formed, the physical properties of the concretes were tested according to the following standards:

[0095] ① Compressive strength test: Refer to GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" to conduct compressive strength test on concrete specimens after standard curing for 28 days.

[0096] ② Gas permeability test: refer to JC / T2758-2023 "Test method for gas permeability of concrete" to treat the concrete specimens after standard curing for 28 days, and then carry out gas permeability test. Use cylindrical concrete specimens with a diameter of 150mm and a height of 50mm, and the test gas circuit pressure is 0.8MPa.

[0097] ③ Shrinkage test: Refer to the contact method in GB / T50082-2009 "Test method for long-term performance and durability of ordinary concrete" to test the drying shrinkage value of concrete on the 7th day.

[0098] The test results are shown in Table 13 below.

[0099] Table 13

[0100]

[0101] From the data in Table 13, it can be concluded that the airtight concrete prepared by the present invention using a special composite cementitious material in combination with diethanol monoisopropanolamine and pre-dispersed carbon nanotubes through the closest packing theory and volume method has greatly improved strength compared with the conventional concrete of the same grade, and the 28d compressive strength can be increased by about 20%, and the gas permeability coefficient is greatly reduced. In Example 2, no gas flow rate is detected under the test pressure of 0.8MPa, and the remaining gas permeability coefficients are 0.004-0.011×10 -18 m 2 It has excellent airtightness and its shrinkage rate is much lower than that of conventional concrete. It can be seen that based on the high-belite cement clinker system, the use of modified components (ferroaluminate cement clinker, light-burned magnesia), submicron materials (submicron silica fume), diethanol monoisopropanolamine and pre-dispersed carbon nanotubes can improve the internal pore structure of concrete to varying degrees, reduce the volume shrinkage of concrete, improve the airtightness and durability of concrete, and thus enhance the adaptability of airtight concrete to complex environments.

[0102] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A low shrinkage and high air tightness concrete, characterized in that: Contains the following ingredients by weight: Special composite cementitious material: 687~746kg / m 3 ; Sand: 848~893kg / m 3 ; Stone: 1036~1091kg / m 3 ; Water: 165~171kg / m 3 ; Water reducing agent: 3.9~4kg / m 3 ; Pre-dispersed carbon nanotubes: 0.687~0.746kg / m 3 ; Diethanol monoisopropanolamine: 0.206~0.224kg / m 3 .

2. The low shrinkage and high air tightness concrete according to claim 1, characterized in that: The special composite gelling material comprises the following components by mass percentage: High belite cement clinker: 55-61wt%; Ferroaluminate cement clinker: 6-12wt%; Light-burned magnesium oxide: 3-5wt%; Submicron silica fume: 7-10wt%; Fly ash: 9-12wt%; Glass powder: 6-8wt%; Gypsum: 3wt%.

3. The low shrinkage and high air tightness concrete according to claim 2, characterized in that: The weight percentages of minerals in the high-belite cement clinker are as follows: C2S: 50-60wt%, C3S: 17-25wt%, C4AF: 13-19wt%, C3A: 2-5wt%; the specific surface area of ​​the high-belite cement clinker is 350-370m 2 / kg, 3d compressive strength ≥12MPa.

4. The low shrinkage and high air tightness concrete according to claim 2, characterized in that: The weight percentages of minerals in the ferroaluminate cement clinker are as follows: 35-55wt%, C2S: 15-35wt%, C6AF2: 15-30wt%; the specific surface area of ​​the ferroaluminate cement clinker is 370-390m 2 / kg, 3d compressive strength ≥42MPa.

5. The low shrinkage and high air tightness concrete according to claim 2, characterized in that: The content of magnesium oxide in the light-burned magnesium oxide is ≥85wt%, the content of active magnesium oxide is ≥65wt%, and the particle size is ≤40μm; the content of SiO2 in the submicron silica ash is >93wt%, and the specific surface area is 23000m 2 / kg, 7d activity index ≥105%; the fly ash is Class I fly ash, with a specific surface area of ​​398m 2 / kg; the glass powder is waste quartz glass powder with a specific surface area of ​​450m 2 / kg; the gypsum is natural gypsum or mixed gypsum, the anhydrite content in the natural gypsum or mixed gypsum is not more than 50wt% of the total gypsum, and the specific surface area of ​​the gypsum is 317~421m 2 / kg.

6. The low shrinkage and high air tightness concrete according to claim 1, characterized in that: The sand is zone II sand which is a mixture of river sand with a particle size of 0-1.18 mm and machine-made sand with a particle size of 0.15-4.75 mm. The river sand and machine-made sand are mixed in a mass ratio of 4:6, and the apparent density is 2573 kg / m 3 , bulk density is 1769kg / m 3 , the fineness modulus is 2.

6.

7. The low shrinkage and high air tightness concrete according to claim 1, characterized in that: The stone is a continuously graded crushed stone with a particle size distribution between 5 and 10 mm, a mud content of 0.7 wt%, a crushing value of 5.2%, and an apparent density of 2782 kg / m 3 , bulk density is 1605kg / m 3 .

8. The low shrinkage and high air tightness concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate greater than 30%; the solid content of the diethanol monoisopropanolamine is ≥85wt%, and the pH value is 10.

24.

9. The low shrinkage and high air tightness concrete according to claim 1, characterized in that: The pre-dispersed carbon nanotubes are obtained by pre-dispersing carbon nanotubes with a length of 100 to 200 μm and a diameter of 7 to 9 nm, and the preparation method is as follows: (1) Weigh carbon nanotubes, polyvinyl pyrrolidone dispersant, and deionized water in a mass ratio of 0.1:0.3:100 for later use; (2) adding carbon nanotubes and polyvinyl pyrrolidone dispersant into deionized water, stirring, sealing, and then ultrasonically treating, followed by high-pressure homogenization to obtain a pre-dispersed solution; (3) freeze-drying the pre-dispersed liquid until deionized water is removed, and then placing it in a high-temperature drying oven to remove the polyvinyl pyrrolidone dispersant to obtain pre-dispersed carbon nanotubes; Preferably, the ultrasonic treatment in (2) is repeated 6 times, and each ultrasonic treatment lasts for 5 minutes; Preferably, the temperature of the high temperature drying oven (3) is 600° C., and the treatment time is 3 h.

10. A method for preparing low shrinkage and high airtightness concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weigh the pre-dispersed carbon nanotubes according to the mass ratio for use, and weigh the special composite gelling material with a mass of 10 times the mass of the pre-dispersed carbon nanotubes and 81.6 times the mass of isopropanol; divide the isopropanol into two parts, add the pre-dispersed carbon nanotubes to one part of the isopropanol, stir to dissolve and ultrasonically disperse to obtain a first mixture, then add the special composite gelling material and the other part of the isopropanol to the first mixture, stir to dissolve and ultrasonically disperse to obtain a second mixture; place the second mixture in a high-temperature drying oven to remove the isopropanol, and obtain a gelling material-CNT dry powder; Preferably, when the pre-dispersed carbon nanotubes are added to a portion of isopropanol, stirred to dissolve and ultrasonically dispersed, the ultrasonic time is 30 minutes; Preferably, when the special composite gelling material and another portion of isopropanol are added to the first mixture, stirred to dissolve and ultrasonically dispersed, the ultrasonic time is 90 minutes; Preferably, the temperature of the high temperature drying oven is 100±5°C and the treatment time is 24h; Step 2: Weigh sand, gravel, water reducing agent, diethanol monoisopropanolamine, water and the remaining special composite gelling material according to the mass ratio for use, and the mass of the remaining special composite gelling material is the total mass of the special gelling material minus the mass of the special composite gelling material corresponding to the gelling material-CNT dry powder prepared in step 1; Step 3: Mix the remaining special composite gelling material in step 2 and the gelling material-CNT dry powder prepared in step 1 evenly; then add the weighed sand and gravel and continue to mix evenly to obtain a mixed dry material; Step 4: The water reducing agent, diethanol monoisopropanolamine and water weighed in step 2 are fully mixed and stirred with the mixed dry materials to obtain a mixture; the mixture is poured into a mold, vibrated to compact, and then covered with a film for curing in an environment of 18°C ​​to 22°C, and low shrinkage and high airtightness concrete is obtained after molding and hardening.

Citation Information

Patent Citations

  • Airtight concrete material and preparation method thereof

    CN110698137A

  • Airtight concrete and preparation method thereof

    CN114133190A

  • High-airtightness concrete and preparation method thereof

    CN114573288A

  • Low-heat corrosion-resistant Portland cement and preparation method thereof

    CN112479610A

  • Capillary crystallization type modified waterproof agent for concrete

    CN113072321A